2004
DOI: 10.1002/mus.20026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on sensory nerve conduction study parameters

Abstract: Research evaluating the changes in nerve conduction with time has been limited to cross-sectional studies. We present a cohort study estimating how sensory nerve conduction study (NCS) parameters change with time when subjects are measured at two time-points. We evaluated 440 working adults by performing median and ulnar antidromic sensory NCS of both hands on two occasions, about 5.4 years (range, 4.3-7.0 years) apart. The rate of change in the NCS parameters was estimated using a mixed-models analysis contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 18 publications
11
44
0
4
Order By: Relevance
“…The results related well with the study by Tong et al 5 who in his prospective cohort study found median sensory velocities to decrease at a rate of 0.14 m/a per year of age, and Werner et al 6 observed a decrease in conduction velocity at a rate of 0.41 m/s per.…”
Section: Discussionsupporting
confidence: 89%
“…The results related well with the study by Tong et al 5 who in his prospective cohort study found median sensory velocities to decrease at a rate of 0.14 m/a per year of age, and Werner et al 6 observed a decrease in conduction velocity at a rate of 0.41 m/s per.…”
Section: Discussionsupporting
confidence: 89%
“…Tong et al (2004) reported the rate of change over time was not affected by hand (dominant versus non-dominant hand), gender, age, or BMI at baseline. The rate of change seen with some of the median nerve parameters was significantly greater than that with the ulnar nerve.…”
Section: David Et Almentioning
confidence: 98%
“…Similar results have been observed by many investigators. Tong et al [15] studied the ulnar sensory CV and it was shown that there was a significant and substantial decline in values of sensory NCV with increasing age in men, whereas, Awang et al [14] reported that only median motor conduction velocity showed a significant reduction with increasing age and concluded that there is no significant effect of age on NCVs except for median motor conduction velocity. Our results show a significant correlation between age and NCV of both median and ulnar nerves.…”
Section: Discussionmentioning
confidence: 99%